Supply-Side Economics in an Integrated World Economy - Tesa, Linda; Mendoza, Enrique (Washington, D.C. : International Monetary Fund, 1993)
The macroeconomic effects of changes in tax and expenditure policies are examined in the context of the competitive equilibrium of a two-country, two-sector model of an integrated world economy. Governments finance purchases and net transfers of tradable and nontradable goods by imposing distortionary taxes on factor incomes and consumption. The model is parameterized and calibrated using data from large industrial economies, including estimates of effective tax rates. Numerical simulations provide estimates of the welfare costs associated with existing distortionary taxes and of the potential gains linked to a more efficient use of these taxes. Welfare gains from tax reforms favoring indirect taxation are substantial. The effects of permanent changes in expenditures depend on their sectoral allocation across tradables and nontradables and on whether they are debtor tax-financed. Trade in goods and assets is very sensitive to fiscal policy changes, but aggregate consumption patterns and welfare implications are not.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet